Relationship Between Nutrient Density and Greenhouse Gas Emissions of Lunches Served at a Large Urban School District. (7th June 2021) - Stern, Alexandra; Richardson, Scott
Abstract: Objectives: This research explored the relationship between greenhouse gas emissions (GHGE) and nutrient density of lunches served at a large urban school district in New England to support menu planning. We hypothesized that nutrient density would be inversely associated with GHGE. Methods: The school district provided information on lunch menus for the 2018–2019 school year. Nutrient density was calculated using the Nutrient Rich Food hybrid score (NRFh). Data on GHGE of foods and agricultural commodities was obtained from the database of Food Impacts on the Environment for Linking to Diets. Under the Offer vs. Serve provision, the school district allows students to select from a variety of lunch combinations to receive a federally reimbursable meal. Federally reimbursable meals must contain at least three meal components and one meal component must be a fruit or vegetable. We calculated the correlation between GHGE and NRFh for all qualifying reimbursable lunch combinations offered during the 2018–2019 school year. Results: We assessed 120, 746 possible reimbursable lunch combinations. The mean GHGE and NRFh of lunches was 0.76 kg CO2 eq lunch −1 and 1.93, respectively. There was a weak negative correlation (r = −0.15) between GHGE and NRFh. Entrees of lunches with the lowest GHGE (≤ 5 th percentile) and highest NRFh (≥ 95 th percentile) contained grains, tofu, and legumes, and in few instances cheese and poultry. Entrees of lunches with the highest GHGE (≥ 95 th percentile) and lowest NRFh (≤ 5 th percentile) contained beef or beef and cheese. Lunches with the lowest GHGE (≤ 5 th percentile) did not include fluid milk. Foods with low NRFh were high in sodium and/or saturated fat, foods with high NRFh contained nuts, seeds, and/or whole grains. Conclusions: Greenhouse gas emissions and nutrient density are only weakly correlated for school lunches; this suggests that nutritiousness of foods should not be used to predict GHGE for school lunches. Our findings show that schools currently provide options which are highly nutritious and produce low GHGE, however the question remains on how to encourage the consumption of these options. Funding Sources: This research was funded by the Danone Institute North America.